Girls’ Tobacco and Alcohol Use During Early Adolescence: Prediction from Trajectories of Depressive Symptoms Across Two Studies - Leve, Leslie D. (2012)
Associations between trajectories of depressive symptoms and subsequent tobacco and alcohol use were examined in two samples of girls assessed at age 11.5 (T1), 12.5 (T2), and 13.5 (T3). Two samples were examined to ascertain if there was generalizability of processes across risk levels and cultures. Study 1 comprised a United States-based sample of 100 girls in foster care; Study 2 comprised 264 girls in a United Kingdom community-based sample. Controlling for T1 aggression and T1 substance use, individual variation in intercept and slope of depressive symptoms was associated with tobacco use at T3 in both samples: greater intercept and increases in depressive symptoms increased the risk for T3 tobacco use. A similar pattern of associations was found for alcohol use in Study 1. The replicability of findings for the prediction of tobacco use from trajectories of depressive symptoms suggests potential benefit in identifying girls with elevated depressive symptoms for tobacco use prevention programs prior to the transition to secondary school.